EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN LISTENING TEAM TERHADAP HASIL BELAJAR PPKn KELAS XI SMAN 7 PONTIANAK - Uswatun Hasanah; Sulistyarini Sulistyarini; Achmadi Achmadi (Universitas Tanjungpura, 2019)
AbstractThis study alms to determine the effectiveness of the use of listening team learning models on the learning outcomes of class XI students on PPKn subject in Pontianak 7 Senior High School. The research method used is the experimental method with the from of research used is pre-experimental design. The research subject were 32 students of class XI IIS 1. The results of data analysis showed that student learning outcomes before and after being given treatment experienced significant differences proven by the result of the average post-test seen before using the listening team learning models which is 62,8. The result of the post-test average of students who were treated with listening team method were increased by 78,9. Based on the test obtained sig(2-tailed) value of 0,000 according to the basic of decision making in the independent T-Test, it can be conclude that Ho is rejected and Ha is accepted. Which means there is a difference between the average pre-test and post-test. Effectivenessof using listening team learning models with on effect size of 2,1 and high category. Keywords:Effectiveness, Listening Team, Learning Outcomes, Civic Education